Impact of Females on the Top Management Team on Firm Performance: Evidence from Chinese Public Firms - Qian, Yuanyuan (2020)
Gender diversity has become a popular issue within corporate government. This paper focus on gender diversity in top management team to explore the influence of gender diversity on firm performance. This research takes a sample of A-share listed companies in Shanghai and Shenzhen stock exchanges spanning 5 years from 2015 to 2019. Despite that fact that the status of Chinese female have largely improved, female still have to face a lot of barriers in their workplace. The finding of this research indicates that female on top management team have a negative effect on firm performance (Tobin’s Q), which is contrary to many other researches.